MALIGNANT INFANTILE OSTEOPETROSIS - Gillani, Saima; Abbas, Zaheer (Journal of Ayub Medical College Abbottabad, 2017)
Malignant infantile osteopetrosis (MIOP) presents early in life with extreme sclerosis of the skeleton and reduction of marrow space. Due to severe sclerosis, signs symptoms of the disease appear as early as neonatal age. As there is defect in bone marrow children present with deficiency of red blood cells, white blood cells and platelets. There is extramedullary haemopoiesis, cranial nerve compressions and severe growth failure. The condition also presents with early and late onset neonatal sepsis and is often lethal in the first decade of life due to secondary infections. The only curative treatment is stem cell transplantation. This is a case report of a new-born who was admitted in nursery of Ayub Teaching Hospital initially with complains of neonatal jaundice and sepsis , and a second time with lower respiratory tract infection. Workup led to diagnosis of osteopetrosis. Keywords: Malignant infantile osteopetrosis; Neonatal sepsis; Osteopetrosis